2012
DOI: 10.1038/hr.2012.142
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of angiotensin II receptor blocker on morning home blood pressure and cardiorenal protection between morning administration and evening administration in hypertensive patients: the COMPATIBLE study

Abstract: Whether the time of administering the angiotensin receptor antagonist olmesartan influences antihypertensive and renoprotective effectiveness remains unclear. This study compared the effects of olmesartan on morning home blood pressure (MHBP), office BP (OBP) and renoprotective parameters between morning and evening administration. A total of 218 patients with primary hypertension were randomly assigned to receive olmesartan once daily in the morning (morning-dose group) or evening (evening-dose group), and 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
(22 reference statements)
0
15
0
1
Order By: Relevance
“…Three cross-sectional studies exploring the efficacy of taking one or more antihypertensive medications at night indicate that bedtime antihypertensive medication reduces asleep SBP, DBP and prevalence of non-dipping, and improves 24-h BP control (8284). A smaller RCT of ARB, found no significant effects of treatment timings on morning home BP or office BP based (85). However, this study did not include overnight or sleep measures of BP and included use of various other medications concurrently.…”
Section: Resultsmentioning
confidence: 99%
“…Three cross-sectional studies exploring the efficacy of taking one or more antihypertensive medications at night indicate that bedtime antihypertensive medication reduces asleep SBP, DBP and prevalence of non-dipping, and improves 24-h BP control (8284). A smaller RCT of ARB, found no significant effects of treatment timings on morning home BP or office BP based (85). However, this study did not include overnight or sleep measures of BP and included use of various other medications concurrently.…”
Section: Resultsmentioning
confidence: 99%
“…Some research groups (18,19) found that, compared with morning dosing, evening dosing of olmesartan was a better dose regimen for the treatment of hypertension, whereas other research groups (20,21) did not support the merits of chronotherapy of olmesartan. In this study, the percent of dipper BP pattern was similar between the olmesartan-M (46%) and olmesartan-E (42%) groups, which suggests that the influence of a dosing-time of olmesartan on BP dipping state was small in hypertensive patients with a non-dipper BP pattern during valsartan treatment at morning.…”
Section: Discussionmentioning
confidence: 96%
“…Also, the intensified inhibitory effect on urinary albumin excretion was suggested to be independent of the circadian variation in BP. Nevertheless, in the recent study16 of olmesartan that similarly compared evening dosing with morning dosing, olmesartan was suggested to show a well-sustained antihypertensive effect independent of dosing time when given once daily. That is, olmesartan significantly reduced the urinary albumin:Cr ratio when given in the morning or in the evening, but there was no significant difference in the reduction of this ratio between the morning and evening dosing groups.…”
Section: Discussionmentioning
confidence: 99%